(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Witchcraft is the practice of, and belief in, magical skills and abilities that are able to be exercised individually or by designated social groups. It is found almost all over the world and the North Eastern region of India is not to exception to it. Missing is the second largest plain tribe of Assam. They inhabit in riverside remote areas of upper Assam distributing in seven districts. This paper deals in witch-hunting practices of the Missing tribe and tries to find out the nature and extend of it. This paper also deals in the role of civil society, Government and NGOs and tries to find out probable remedy to it.